2005
DOI: 10.1007/s00442-005-0004-9
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen outputs from fecal and urine deposition of small mammals: implications for nitrogen cycling

Abstract: The contribution of small mammals to nitrogen cycling could have repercussions for the producer community in the maintaining or perhaps magnifying of nitrogen availability. Our objective was to model nitrogen outputs (deposition of feces and urine) of small mammals in an old-field ecosystem and estimate the amount of fecal and urinary nitrogen deposited annually. To address this objective, we used models from laboratory studies and combined these with data from field studies to estimate dietary nitrogen and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 49 publications
(50 reference statements)
0
29
0
Order By: Relevance
“…Rodents and shrews play important ecological roles by sustaining multiple terrestrial and aerial predators (Andersson and Erlinge 1977) and by contributing to the cycling of nutrients (Clark et al 2005). Furthermore, they act as useful indicators of ecological integrity and can be used to predict environmental change (Avenant and Cavallini 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Rodents and shrews play important ecological roles by sustaining multiple terrestrial and aerial predators (Andersson and Erlinge 1977) and by contributing to the cycling of nutrients (Clark et al 2005). Furthermore, they act as useful indicators of ecological integrity and can be used to predict environmental change (Avenant and Cavallini 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that, contrary to our a priori assumptions, at higher dietary nitrogen, individuals may face increasing energetic demands from the excretion of excess nitrogenous compounds, which may lead to decreased immune function. Although we did not measure metabolic rate or nitrogen excretion during this study, a concurrent study from the same lab measured nitrogen excretion in the same species (Parsons 2001;Clark et al 2005). Parsons (2001) found that changes in liver and gut morphology were associated with both maternal and offspring dietary nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Parsons (2001) found that changes in liver and gut morphology were associated with both maternal and offspring dietary nitrogen. Clark et al (2005), using results from Parsons (2001), found that increasing dietary nitrogen is associated with increased urinary nitrogen output and that with increasing dietary nitrogen, harvest mice increase nitrogen output faster than cotton rats. This provides indirect support for the hypothesis that the energy needed to eliminate excess nitrogen may reduce energy available for immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A complementary approach to estimating frass N inputs is to scale individual N flux to the community level using general models of individual flux and information about community structure. This strategy has been used to study N flux by a variety of aquatic (Peters and Rigler 1973;Ejsmont-Karabin 1984;Grimm 1988;Wen and Peters 1994;Vanni et al 2002) and mammalian herbivores (Clark et al 2005), but this approach has not been used with herbivorous insects.…”
Section: Introductionmentioning
confidence: 99%